Self-Concept and Physical Activity: Differences Between High School and University Students in Spain and Portugal - Onetti-Onetti, Wanesa; Chinchilla-Minguet, José Luis; Martins, Fernando Manuel Lourenço; Castillo-Rodriguez, Alfonso (Frontiers in Psychology, 2019)
The period of adolescence stands out as a critical and decisive phase, first because it leaves its mark on personality development, which is affected by psychosocial factors, and secondly, because the healthy lifestyle habits acquired during this stage form a foundation for adulthood. The objective of the present study was, firstly to evaluate the levels of participation in physical activities (PA) and of self-concept during the transition from high-school to university, and secondly to find relationships between these psycho-physical variables. Four hundred forty adolescents ranging in age from 16 to 20 years, from Spain and Portugal, participated in this study (cross-sectional design). The IPAQ and Self-Concept Form-5 questionnaires were used. The results demonstrated some differences; the Portuguese university students had lower scores in the academic, emotional and physical dimensions and vigorous PA but higher sitting time, walk and moderate PA than Portuguese high-school students. In addition, Spanish university students had lower self-concept scores although higher practice of PA and lower sitting time than Spanish high-school students (p<.05). On the other hand, a positive relationship was found between different dimensions of self-concept and levels of PA, while the relationship between these dimensions and the time the adolescent spent sitting was negative. In conclusion, the university students have lower scores of self-concept dimensions (in general) and the practice of PA is higher in Spanish university students, confirming the clear presence of differences between both educational stages. The relationship between the dimensions of self-concept in general and the level of PA was positive (following the contributions of Marsh).